Above and beyond senescence and CAR T cell: advances and future perspectives - Rosas-Campos, Rebeca; Arceo-Orozco, Scarlet; Sandoval-Rodriguez, Ana; Madrigal, Jose Alejandro; Armendariz-Borunda, Juan (Frontiers in Immunology, 2025)
Cellular senescence is a complex biological process that contributes to the progression of age-related diseases. Senescent cells accumulate over time and secrete proinflammatory factors that disrupt tissue homeostasis and promote chronic diseases. Initially created for cancer immunotherapy, chimeric antigen receptor (CAR) T cell therapy has recently been repurposed at the preclinical level to eliminate senescent cells by recognizing senescence-associated surface markers. Recent preclinical studies have demonstrated the feasibility of anti-uPAR and anti-NKG2D CAR T cell-based approaches for eliminating senescent cells in preclinical models of fibrosis, metabolic disorders, and natural aging, resulting in reduced fibrotic burden, improved metabolic parameters, and enhanced tissue function. However, several challenges remain in their clinical applicability, including the identification of specific and universal senescence markers, potential off-target effects, and long-term safety concerns. Additionally, immunosenescence, an age-related decline in immune function, poses challenges for CAR T cell therapy in elderly patients. This review discusses recent advancements in CAR T cell therapy for senescence clearance, highlighting key molecular targets, preclinical findings, and future research directions. Despite their promise, a significant translational gap persists, and further research is required to improve the specificity, efficacy, and readiness for future human clinical trials.